Why a second look might be worth it: immuno-modulatory therapies in the critically ill patient - Siegler, Benedikt Hermann; Brenner, Thorsten; Uhle, Florian; Weiterer, Sebastian; Weigand, Markus A.; Hofer, Stefan (Journal of thoracic disease, 2016)
Sepsis and septic shock are associated with high mortality rates and remain a serious menace for the critically ill patient. Concurrent activation of pro- and anti-inflammatory pathways and an excessive cytokine release represent initial key features in the deregulation of the humoral and cellular antimicrobial defense. Research of the last decades addressed both the ebullient inflammation as well as the resulting long-term failure of the host immunity. While the reestablishment of an adequate immune-competence is still under investigation, many promising experimental trials to limit the inflammatory response during sepsis were challenged by missing beneficial effects in clinical studies. Nevertheless, due to advanced knowledge about the complex regulation of inflammatory mediators and their overlapping involvement in other potentially life-threatening diseases, further evaluation of these approaches in relevant subgroups could help to identify critically ill patients with potential benefit from anti-inflammatory therapies.